PERSPEKTIF ISLAM TERHADAP NILAI MORAL DALAM CERPEN DAULAH AL-‘ASHĀFĪR KARYA TAUFĪQ AL-CHAKĪM (ANALISIS SEMIOTIKA ROLAND BARTHES) - Siti Umi Kasanah, Reza Sukma Nugraha (CMES (Center of Middle Eastern Studies), 2019)
This study aims to describe the Islamic perspective on moral values in the short story Daulah Al-‘Ashāfīr by Taufīq Al-Chakīm. The method used in this study is a qualitative descriptive method. The object of this research is the Daulah Al-Ashāfīr short story by Taufīq Al-Chakīm using Roland Barthes's Semiotic theory. The data used is the text in the form of quotations that show moral values in the Daulah Al-Ashāfīr. Analysis is done by reading, then recording things that show moral values in the Daulah Al-Ashāfīr. Furthermore, collecting secondary data that supports the research. Then analyze the moral values of Daulah Al-Ashāfīr by using Roland Barthes's semiotic theory and proceed with an Islamic perspective on that value. Finally, make a conclusion. The results of the study show that moral values in the short story Daulah Al-Ashāfīr by Taufīq Al-Chakīm are divided into three, namely (1) religious moral values, (2) social moral values, (3) and individual moral values. All three moral values are in accordance with Islamic teachings, there is human relations with God, human relations with others, and human relations with yourself.